2023
DOI: 10.1007/s40572-023-00394-8
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Exposure to Synthetic Phenols and Phthalates from Dietary Intake and Personal Care Products: a Scoping Review

Abstract: Purpose of Review A scoping review was conducted to identify interventions that successfully alter biomarker concentrations of phenols, glycol ethers, and phthalates resulting from dietary intake and personal care product (PCPs) use. Recent Findings Twenty-six interventions in populations ranging from children to older adults were identified; 11 actively removed or replaced products, 9 provided products containing the chemicals being studied, and 6 were ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…However, we did find several studies reported findings where the intervention did not have a significant effect on all target chemicals, 88 and one intervention led to an increase in exposure. 89 While the number of intervention studies aimed at reducing EDC exposures in general is increasing and are the topic of other recent reviews, 81 83 our study focused specifically on phthalates and the most common bisphenols and examined multiple types of interventions, not just dietary or medical. We further did not limit our review to a specific stage in the life course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did find several studies reported findings where the intervention did not have a significant effect on all target chemicals, 88 and one intervention led to an increase in exposure. 89 While the number of intervention studies aimed at reducing EDC exposures in general is increasing and are the topic of other recent reviews, 81 83 our study focused specifically on phthalates and the most common bisphenols and examined multiple types of interventions, not just dietary or medical. We further did not limit our review to a specific stage in the life course.…”
Section: Discussionmentioning
confidence: 99%
“…If a discrepancy arose, the two team members discussed the issue(s), and any remaining discrepancies were then discussed among all authors so a consensus could be reached. We additionally cross-checked the reference lists of all included papers and related reviews 81 83 to ensure that all relevant studies were captured in our review. Any identified articles were entered into CADIMA and underwent the same process of screening using the selection criteria discussed above.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there is a widespread increasing presence of BPA in everyday items (e.g., food containers, food packaging film, toys, pens, kitchen utensils, medical products/devices, dental supplies, cosmetic supplies, personal care products, toothpaste, medications, helmets, cell phones, thermal paper (e.g., receipts, tickets, boarding passes), construction materials, CD/DVDs, and many others [ 1 , 3 , 4 , 11 , 13 , 19 , 20 , 21 , 22 , 23 , 27 , 38 , 78 , 79 , 80 ]. They are commonly used as plasticizers, solvents, fixatives, color developers (in thermal paper), cigarette filters, antimicrobial agents, or commonly used preservatives [ 13 , 68 , 80 , 110 ].…”
Section: Sources In Food/packagingmentioning
confidence: 99%
“…2023/2006; (EC) 1907/2006; (EC) No. 1935/2004), among others, are still of great concern with regard to BPA, as they do not take into account the latest knowledge on, for example, dose–response relationships, mixtures resulting from the joint use of products, and exposure effects occurring at different stages of human development [ 110 ]. Meanwhile, Commission Regulation (EU) No.…”
Section: Guidance From Various International Organizationsmentioning
confidence: 99%
See 1 more Smart Citation